ANALYSIS OF IOT-BASED COMMUNICATION MEDIA IN IMPROVING INTERACTION IN SMART HOME AND SMART OFFICE - Boy Firmansyah; Iswahyu Pranawukir; Nuraini Purwandari (Yayasan Nuraini Ibrahim Mandiri, 2025)
This study aims to analyze the role of Internet of Things (IoT)-based communication media in improving the quality of interaction and communication efficiency in smart home and smart office environments. Along with the development of digital technology, IoT devices have become a communication bridge between humans and automated systems, enabling more responsive and real-time control, monitoring, and collaboration. The method used in this study is a qualitative approach with case studies and in-depth interviews with users and managers of smart home and smart office systems. The results of the study show that IoT-based communication media, such as virtual assistants, automatic sensors, and integrated management platforms, are able to improve comfort, security, and productivity through faster and more personal interactions. However, this study also found challenges in terms of data security and interoperability between devices. Thus, the use of IoT as a communication medium needs to be balanced with strengthening security systems and technology standardization in order to support optimal interactions in today's smart ecosystem.